Sistema óptico de projeção a laser para análise da superfície das pregas vocais em imagens laringoscópicas - Medeiros, Jacilene Martins (Universidade Federal de São Carlos, 2021)
When understanding the acoustic production of the human voice and its dysphonia, factors such as characteristics and dimensions of the vocal folds are relevant. Previous studies show that images of the glottic surface, seen through laryngoscopy technique, are shaped according to their geometric shapes and shades of color and brightness. However, clinical examinations in general are still performed subjectively and present challenges, especially regarding the detection of the position of anomalies. Therefore, the objective of this work is to propose an optical laser projection system, capable of detecting the surface characteristics of pathological vocal folds and estimating their quantitative parameters. This system comprises a structured white light source, a diffractive optical element (DOE) and a high-resolution camera, which together are able to project onto the photographed vocal folds a regular array of pixels measuring 12 x 12 light spots . Thus, by superimposing the DOE metric on vocal fold surface images, parameters such as position and dimension can be quantified. In order to minimize operating costs, the UPL DOE project was simulated and based on the scalar theory of Fourier diffraction. This master’s research analyzed the laryngoscopic images of 3 patients, p1, p2 and p3 , with polyps, cyst and leukoplakia, respectively. In addition to simulating the system, to validate the proposal, a prototype was developed, with a commercial UPL and molds of the glottic surface of each patient. The image processing, simulation and prototype were centered on the semi-automatic method of the watershed. Therefore, with a diffraction grating of 73 % efficiency, two polyps, a cyst and a leukoplakia were detected with dimensions of 9.73 x 8.82 ±10⁻⁵ mm and 24.06 x 8.97 .73 ±10⁻⁵ mm; 4.12 x 10.00 ±10⁻⁴ mm and 20.03 x 16.30 ±10⁻⁵ mm, respectively.. This study demonstrated that the proposed system can be considered a suitable tool for vocal fold surface analysis, either as a treatment or as prognosis of pathologies, seeking to improve the quality of life of patients.
Optical laser projection system for surface analysis of vocal folds in laryngoscopic images
Keywords: Distúrbio de voz; Laringoscopia quantitativa; Sistema óptico de projeção a laser; Método divisor de águas; Voice disorder; Quantitative laryngoscopy; Optical laser projection system; Watershed method; CIENCIAS EXATAS E DA TERRA; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO